O ensino de PLE pelo texto multimodal como semiose ilimitada - Gois, Elaine Vieira (2016)
This work has the multimodal text and its interfaces with two semiotic codes: word and still image as theme. Currently it lives a strongly trend marked by approximations between relationship the "Writing civilization" and the "civilization image" in multimodal texts, whose reading and construction of meaning, by the user in general and, in particular, by the PLE learner involves the use of a semiotic approach that offers conditions to explain the peculiarities of each of the co-occurrent code in a multimodal text, as well as to establish possible relationships between them.Among the theoretic models of semiotic, we have opted for the ModeloSemânticoReformulado (MSR), proposed by Eco, in his General Treaty of Semiotic, in which the author recasts the previous model of Katz and Fodor, in association, in this Thesis, with categories of indexicals referential relations between word and image, and other forms of referential relations between these two semiotics in the plans of content and expression, presents in Santaella and Nöth. To this end, it is conceived the multimodal text within a process of unlimited semiosis, initially proposed by Peirce and later taken over by Eco. Was selected as corpus an advertising campaign of Sadia company, it consists of six commercials, in a view that advertising discourse is guided by the maintenance of social cognition landmarks, which it favors the process of meaning by the use of lexias with a high degree of lexicalization and by images that often corroborate certain visions of the sociocultural world of a society or certain social groups. In this sense, the corpus choice has as main objective the appreciation of communicative approach to PLE teaching, based on / by interculturality, by the relational route between word and image in multimodal texts of advertising genre. The obtained results point to the use of multimodality as one of the contributions to the foreign learner ressemantize encyclopedic sememes in the target language, associated with the images, by the cultural exchanges that it establishes with the social representations of their mother language.